Rotator Cuff Matrix Augmentation and Interposition: A Systematic Review and Meta-analysis. Issue 6 (May 2019) - Bailey, James R.; Kim, Christopher; Alentorn-Geli, Eduard; Kirkendall, Donald T.; Ledbetter, Leila; Taylor, Dean C.; Toth, Alison P.; Garrigues, Grant E.
Background: Surgical management of rotator cuff tears is controversial and complex, ranging from nonoperative management to reverse shoulder arthroplasty. Purpose: To systematically review and evaluate the outcomes of graft augmentation or interposition versus rotator cuff repair (RCR) alone and evaluate via meta-analysis whether the use of a graft leads to superior outcomes versus RCR alone. Study Design: Systematic review and meta-analysis. Methods: An electronic literature search (Medline, Embase, CINAHL) was conducted. Studies with a minimum follow-up of 1 year and minimum sample size of 10 that provided clinical results of RCR or rotator cuff reconstruction using any type of augmentation tissue or matrix were included. Methodological quality was evaluated by assessment of the risk of bias in the included studies. Studies comparing outcomes of RCR with graft augmentation or interposition versus repair alone (control group) were subjected to meta-analysis. Results: The authors identified 774 articles and included 36 in the systematic review; 5 of the 36 studies underwent meta-analysis. Except for one outcome measure in a single study, all surgical interventions (RCR alone, RCR with augmentation, and RCR with interposition) improved clinical scores and outcome measures. Because of variability in study outcomes, no graft option was found to be superior. Compared with RCR alone, graft augmentation or interposition provided significantly lower retear rates ( P = .05) and higher American Shoulder and Elbow Surgeons (ASES) scores ( P = .005), but improvements in UCLA (University of California, Los Angeles) scores ( P = .29) and pain scores ( P = .1) did not reach statistical significance. Conclusion: In the meta-analysis, graft augmentation or interposition appeared to provide a lower retear rate and improved ASES scores when compared with RCR alone. Future prospective, randomized, controlled, and appropriately powered trials are needed for more definitive recommendations.